THE ENZYMES OF SOME ELASMOBRANCHS FROM BOMBAY. I. PROTEASES - Ghanekar, D S; Bal, D V (Indian Journal of Fisheries, 2016)
AT present a large amount of data on the enzymes of various tissues of higher animals, plants, yeasts, molds and bacteria is available. However, no detailed study of the enzymes of fish has been reported in the literature except the crystallization of salmon pepsin (Norris and Elam, 1940) and investigations on shark gastric proteinase (Sprissler, 1942) smd shark pancreatic proteinase (Boos, 1943).